LARVICIDAL ACTIVITY OF LANTANA INDICA AND VITEX NEGUNDO ON CULEX QUINQUEFASCIATUS - K, Rathnasagar; Anand, Thiyagaraj (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The activity of two different leaf extracts of Lantana indica and Vitex negundo is tested against the 3rd and 4th instar Culex quinquefasciatus larvae to evaluate the potency of the extracts as a larvicide and to find an ecologically sustainable alternative to chemical insecticides. A bioinformatics screening approach was performed to evaluate the in vivo results. Methods: The obtained larvae's from nearby water sources were tested with N, N-diethyl-meta-toluamide (DEET) as the positive control which is the commercial chemical mosquito repellent and the solvents used for the respective plant extracts act as the negative control. Petroleum ether (PE), ethyl acetate (EA) and an aqueous (AQ) extract were prepared for both L. indica and V. negundo extracts, and its larvicidal activity was tested. A docking based approach was used to study the inhibitory effect of known active compounds from L. indica and V. negundo against acetylcholine esterase (AChE) and sterol binding protein as targets. Results: On comparing the results between three plants extract for its larvicidal activity, the EA extract of V. negundo and L. indica is found to be potent with a low LC50 value. Further, the docking studies between active compounds of L. indica and V. negundo with AChE and Sterol binding protein as targets showed that the compound tangeritin-1 had a good docking score compared to DEET and could be a natural alternative for larvicidal activity in the mosquito. Conclusion: Individual activity of tangeritin-1 could be further studied with mosquito mortality studies and molecular simulations and develop tangeritin-1 as a potential larvicidal compound for commercial use.